ANALISIS KOMUNIKASI ORGANISASI DAN MOTIVASI KERJA KARYAWAN DI KUMALA DEWATA - Nyoman Dinda Suhartini, (2020)
The research was conducted because this wanted to see whether organizational communication carried out by Kumala Dewata had been running effectively so as to increase employee motivation. How do internal parties feel about the ongoing communication in Kumala Dewata. The purpose of this study is to find out how Kumala Dewata in creating effective organizational communication. Data collection techniques used were in-depth interviews (in-depth interviews) and direct observation to the Kumala Dewata office. The results showed that organizational communication carried out in Kumala Dewata was not effective so it could not increase employee motivation.